Effect of Bleaching on Color Change and Surface Topography of Composite Restorations - Gunjan Pruthi; Veena Jain; H. C. Kandpal; Vijay Prakash Mathur; Naseem Shah (International Journal of Dentistry)
This study was conducted to determine the effect of 15% carbamide peroxide bleaching agent on color change and surface topography of different composite veneering materials (Filtek Z350 (3M ESPE), Esthet X (Dentsply India), and Admira (Voco, Germany). Methods. 30 samples were fabricated for evaluation of color change using CIELAB color system and Gonioreflectometer (GK 311/M, ZEISS). 45 disc-shaped specimens were made for evaluation of surface topography after bleaching (Nupro White Gold; Dentsply) using SEM. Statistical analysis. One way ANOVA and Multiple comparison tests were used to analyze the data. Statistical significance was declared if the P value was .05 or less. Results and conclusion. All the specimens showed significant discoloration (ΔE>3.3) after their immersion in solutions representing food and beverages. The total color change after bleaching as compared to baseline color was significant in Filtek Z350 (P=.000) and Esthet X (P=.002), while it was insignificant for Admira (P=.18). Esthet X showed maximum surface roughness followed by Admira and Filtek Z350. Bleaching was effective in reducing the discoloration to a clinically acceptable value in all the three groups (ΔE<3.3).